2015
DOI: 10.1002/cbin.10495
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow mesenchymal stem cells could acquire the phenotypes of epithelial cells and accelerate vaginal reconstruction combined with small intestinal submucosa

Abstract: Grafting material for vaginal reconstruction commonly includes the bowel, peritoneum, skin, and amniotic membrane. Bone marrow mesenchymal stem cells (MSCs) have the potential of multilineage differentiation into a variety of cells and have been widely explored in tissue engineering. In the current study, we examined whether MSCs could be differentiated to vaginal epithelial cells (VECs) upon co-culturing with VECs. We also examined whether Wnt/β-catenin signaling pathway is implicated in such differentiation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 31 publications
1
7
0
1
Order By: Relevance
“…MSCs are widely used in tissue engineering. In the present study, we found that an epithelium had covered the whole neovagina at the 4th week, which is consistent with our previous study , and we found that the epithelium became more mature at the 12th week. More smooth muscle and nerve tissue were found in the neovaginas of the SIS+MSCs group than in those of the SIS group.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…MSCs are widely used in tissue engineering. In the present study, we found that an epithelium had covered the whole neovagina at the 4th week, which is consistent with our previous study , and we found that the epithelium became more mature at the 12th week. More smooth muscle and nerve tissue were found in the neovaginas of the SIS+MSCs group than in those of the SIS group.…”
Section: Discussionsupporting
confidence: 93%
“…All relevant protocols were approved by the Institutional Animal Care and Use Committee of Hebei Medical University. The isolation and culture of bone marrow‐derived MSCs was performed as described previously . Briefly, Sprague‐Dawley rats, 2–5 weeks old, were sacrificed by cervical dislocation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Vaginal agenesis, the congenital underdevelopment of the vagina, occurs in 1 out of 5000 females. [55][56][57] Various biomaterials have been used to fabricate vaginal grafts, including dermal matrix, 55,56,[58][59][60][61] SIS, 53,[62][63][64][65][66][67] and human amniotic membrane. 68 Recently, there have been several investigators that explored different biomaterials and cell sources to create tissue engineered constructs for vaginal agenesis therapies (Table 3).…”
Section: Cervicovaginal Tissuementioning
confidence: 99%